2022
DOI: 10.1038/s41467-022-30068-2
|View full text |Cite
|
Sign up to set email alerts
|

Glycaemic control is associated with SARS-CoV-2 breakthrough infections in vaccinated patients with type 2 diabetes

Abstract: Patients with type 2 diabetes (T2D) are characterized by blunted immune responses, which are affected by glycaemic control. Whether glycaemic control influences the response to COVID-19 vaccines and the incidence of SARS-CoV-2 breakthrough infections is unknown. Here we show that poor glycaemic control, assessed as mean HbA1c in the post-vaccination period, is associated with lower immune responses and an increased incidence of SARS-CoV-2 breakthrough infections in T2D patients vaccinated with mRNA-BNT162b2. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 29 publications
3
40
0
1
Order By: Relevance
“…Van Praet et al showed that peripheral blood mononuclear cells (PBMCs) from patients with diabetes produced less interferon gamma (IFNg) upon SARS-CoV2 glycoprotein stimulation (22). Marfella et al showed that CD4 + T cell responses were impaired in patients with type 2 diabetes who had poor glycaemic control (20,23). Notably, T cell biology is complex with distinct effector and memory T cell subsets performing discrete roles in immunity (24).…”
Section: Introductionmentioning
confidence: 99%
“…Van Praet et al showed that peripheral blood mononuclear cells (PBMCs) from patients with diabetes produced less interferon gamma (IFNg) upon SARS-CoV2 glycoprotein stimulation (22). Marfella et al showed that CD4 + T cell responses were impaired in patients with type 2 diabetes who had poor glycaemic control (20,23). Notably, T cell biology is complex with distinct effector and memory T cell subsets performing discrete roles in immunity (24).…”
Section: Introductionmentioning
confidence: 99%
“…These positive and negative factors are consistent with previous studies (22, 25-28). In addition, diabetes and autoimmune diseases have been reported to be risk factors for breakthrough infections (29, 30). Considering that individual antibody titers are partially predictive of the likelihood of breakthrough infections (31, 32), this suggests that our antibody score could also be used as a risk score for breakthrough infections.…”
Section: Discussionmentioning
confidence: 99%
“…Older age, male sex, and the presence of age-related diseases are the strongest risk factors for severe outcomes in patients with coronavirus disease (COVID)-19, the disease driven by the infection of SARS-CoV-2 [ 98 ]. All three of these conditions are characterized by a more pervasive status of inflammaging, which predisposes patients with these features to develop excessive inflammation coupled with an inefficient immune-mediated viral neutralization, two phenomena held to drive severe COVID-19 outcomes [ 99 , 100 , 101 ].…”
Section: Effect Of Sglt-2i On Covid-19 Outcomesmentioning
confidence: 99%